2015
DOI: 10.1136/acupmed-2014-010740
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Sensitive Moxibustion in Patients with Osteoarthritis of the Knee: A Three-Armed Multicentre Randomised Active Control Trial

Abstract: The trial was registered at Controlled Clinical Trials: ChiCTR-TRC-09000600.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Overall, 3 trials were performed in China, and 1 was performed in Korea. 23 The moxibustion treatments in 3 randomized clinical trials (RCTs) 2022 were based on the traditional Chinese medicine theory as the guide for the implementation procedures. The points were chosen according to the traditional Korean medicine in the other RCT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 3 trials were performed in China, and 1 was performed in Korea. 23 The moxibustion treatments in 3 randomized clinical trials (RCTs) 2022 were based on the traditional Chinese medicine theory as the guide for the implementation procedures. The points were chosen according to the traditional Korean medicine in the other RCT.…”
Section: Resultsmentioning
confidence: 99%
“…The mean duration of follow-up ranged from 3 to 28 weeks. The intervention typesin the control groups were sham moxibustion in 2 studies, 20,21 intraarticular sodium hyaluronate in 1 study, 22 and usual care (UC) in 1 study. 23 One RCT tested the positive effects of moxibustion on KOA, utilizing the following 3 randomized groups: HSM group, conventional moxibustion group, and intraarticular sodium hyaluronate control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Complementary and alternative therapies, including acupuncture and moxibustion, may be employed as adjuvant treatments. [19][20][21][22][23][24] It has been reported that acupuncture is effective for knee pain management, especially for chronic knee pain and knee pain after total knee arthroplasty. [25][26][27] The potential mechanisms of acupuncture underlying its beneficial effects on knee pain may include prevention of further cartilage erosion as well as more conventional analgesic mechanisms.…”
Section: Introductionmentioning
confidence: 99%